Fundamentals of computing : (McGraw-Hill, 1995)
This book integrates the study of problem solving and C++ programming with its underlying theory, unites logic and programming with topics in computer organisation, introduces basic concepts of objects and classes as well as the social context of the discipline through a treatment of intellectual property and software reliability issues.